Characterization of engineering properties of weak subgrade soils with different pozzolanic & cementitious additives - Inayat Ur Rahman; Muhammad Raheel; Muhammad Wajahat Ali Khawaja; Rawid Khan; Jie Li; Arsalaan Khan; Muhammad Tariq Khan (Case Studies in Construction Materials, 2021)
The strength of subgrade layer plays an important role in achieving a sound and economic pavement design. To explore novel methods for improving the engineering properties of weak subgrade soils, this research study used bentonite, a naturally occurring pozzolanic material and compared its performance with commercially available cementitious materials such as cement and lime. For this purpose, these pozzolanic and cementitious additives were added in different percentages to representative weak subgrade soils for studying different parameters such as Optimum Moisture Content (OMC), Maximum Dry Density (MDD), California Bearing Ratio (CBR) and Resilient Modulus (MR). The experimental results revealed that the addition of cement lowered the OMC and increased MDD substantially compared to lime and bentonite. The CBR of soil samples enhanced by almost 19 times for 12 % cement addition, followed by lime, which enhanced CBR by 15 times for 15 % addition. The addition of bentonite and lime also enhanced the MR values by almost 3 and 7 times the control specimen for 15 % bentonite and 8% lime addition, respectively. These results indicate that; similar to cement and lime, addition of bentonite can improve the mechanical properties of weak soils by reducing its plasticity and swell potential.